Status and issue of scoliosis screening in Akita - Wakabayashi, Rena; Hongo, Michio; Shimada, Yoichi; Kudo, Daisuke; Misawa, Akiko; Kimura, Ryota; Miyakoshi, Naohisa (Journal of Spine Research, 2023)
Introduction: In Akita Prefecture, school screening using the Moiré topography have been conducted since 1984, and have been continued after the start of musculoskeletal screening. In this study, we compared the results of the scoliosis examination using the Moiré screening with those of the musculoskeletal screening using data provided by the Akita City Board of Education.Methods: From 2017 to 2020, 1,442 patients with spinal column findings in musculoskeletal screening and 474 patients with Moiré screening findings underwent secondary examination.Results: The positive predictive value for the Cobb angle of 10 degrees or more was 39% in the musculoskeletal screening, and 60% in the Moiré screening. The positive predictive value of scoliosis in junior high school students was 57% for the musculoskeletal screening, which was similar to that for the Moiré screening. 13% of the diagnosed cases were newly positive for the musculoskeletal screening and 87% were continuously positive, and most of the cases were diagnosed with scoliosis by the Moiré screening.Conclusions: The results of this study have once again demonstrated the usefulness of Moiré screening in comparison with musculoskeletal screening. In order to promote the use of Moiré screening, it is necessary to improve the follow-up system after the screening. In addition, it is necessary to approach and cooperate with boards of education and medical associations for the development of medical checkups to resolve issues such as the protection of personal information in order to provide feedback on the results of medical checkups.